Desain Media Pembelajaran melalui E-cerita Bergambar pada Pembelajaran Qira’ah - Mahira, Putri Nanda; Hayati, Salma (Universitas Negeri Padang, 2025)
The goal of this project is to create the E-Story Picture design as a cutting edge teaching tool to enhance MTs level Arabic language acquisition. The four steps of the Design Based Research (DBR) method needs analysis, design, evaluation, and distribution are used in this study. Interviews and questionnaires were employed as data collection tools. Data analysis used qualitative and quantitative analysis. The results of the problem analysis in learning are the low interest in reading in Indonesia caused by several factors. To increase interest in reading, several strategies can be applied such as creating interesting learning media, and giving awards to students who are active in participating in reading activities. The results of the illustrated e-story design have produced teaching material products that contain Arabic learning materials with the theme “Ashabul Fil” which are interactive, contextual, and interesting. Validation of design products is carried out by 4 experts. The results of the experts' assessment of the design of Arabic illustrated e-stories from the aspects of content and language obtained a score of 97%, and from the design aspect obtained a score of 96%, so that the designed illustrated e-stories were declared feasible to use by following the suggestions for improvement from the experts. The results of the teacher's assessment of the design of the illustrated e-story obtained a score of 94%. The results of the illustrated e-story design use hyperlinks and are published by distributing them to Arabic language teachers. Thus, the design of illustrated e-stories that have been designed can be used as teaching materials in learning Arabic at the Madrasah Tsanawiyah (MTs) level.